Cross-Pathway Regulation: Tryptophan-Mediated Control of Histidine and Arginine Biosynthetic Enzymes in Neurospora crassa - Carsiotis, M. (1974)
In Neurospora crassa, the starvation of tryptophan mutants for tryptophan resulted in the derepression of tryptophan, histidine, and arginine biosynthetic enzymes. This tryptophan-mediated derepression of histidine and arginine biosynthetic enzymes occurred despite the fact that the tryptophan-starved cells had a higher intracellular concentration of histidine and arginine than did nonstarved cells.